Application of Contrast‐Enhanced Real‐time 3‐Dimensional Ultrasound in Solid Abdominal Organ Trauma. (14th November 2019) - Feng, Cong; Wang, Libo; Huang, Sai; Wang, Lili; Zhou, Xuan; Cui, Xiang; Chen, Li; Lv, Faqin; Li, Tanshi
Abstract : Objectives: To determine whether real‐time 3‐dimensional ultrasound (RT3DUS) could provide additional information on early detection and evaluation in the management of solid abdominal organ trauma based on an animal model. Methods: Nine bleeding lesions were developed in the livers (n = 3), kidneys (n = 3), and spleens (n = 3) from 9 pigs. An ultrasound contrast agent was administered intravenously (liver, 0.025 mL/kg; kidney, 0.008 mL/kg; and spleen, 0.013 mL/kg) after an unenhanced 2‐dimensional ultrasound (2DUS) examination (B‐mode and color Doppler). After contrast agent injection, bleeding lesions were imaged by 2DUS and sequentially imaged by 3‐dimensional static ultrasound (3DSUS) and RT3DUS to identify active bleeding, observe the relationship between bleeding lesions and peripheral blood vessels, and evaluate the spatial scope of the bleeding lesions in the organs. Results: For the identification of active bleeding, there was no statistical difference in contrast‐enhanced 2DUS, 3DSUS, and RT3DUS. For observation of the relationship between bleeding lesions and peripheral blood vessels, RT3DUS performed statistically better than 2DUS ( P  < .05), as reconstructed RT3DUS could show more information about the relationship. For the evaluation of the spatial scope of the bleeding lesion in the organ, RT3DUS also performed statistically better than 2DUS from the multiplanar observation by postprocessing of the 3‐dimensional real‐time volumes ( P  < .05). Conclusions: Real‐time 3‐dimensional ultrasound improves early detection and evaluation of solid abdominal organ trauma and provides additional information over the current contrast‐enhanced 2DUS.